Comparison of antimicrobial resistance patterns and phage types of Salmonella Typhimurium isolated from pigs, pork and humans in Belgium between 2001 and 200631075 - Van Boxstael,S; Katelijne Dierick; Van Huffel,X.; Uyttendaele,M.; Dirk Berkvens; Herman,L.; Sophie Bertrand; C. Wildemauwe; Boudewijn Catry; Butaye,P.; Hein Imberechts (Food research international, 2012)
Infections with non-typhoid
Keywords: 2001; 2006; a; acid; Agreement; Ampicillin; Antimicrobial; Antimicrobial resistance; Antimicrobials; AS; Belgium; cephalosporin; Cephalosporins; Chloramphenicol; Combination; Common; Comparison; CONSUMPTION; Countries; Fluoroquinolones; Group; hazard; health; Human; Humans; Hypothesis; incidence; INFECTION; infections; IS; Less; n; Nalidixic Acid; observed; ORIGIN; pathogen; Pathways; pattern; PATTERNS; period; Phage type; Pig; Pigs; Pork; resistance; S; Salmonella; Salmonella typhimurium; Spread; Streptomycin; study; Tetracycline; Type